MAPPING THE IDEOLOGY OF CONSTITUTIONAL JUDGES AND THE PRESIDENT OF THE REPUBLIC OF INDONESIA: AN ANALYSIS OF DECISION CONSIDERATIONS - Munawir, Yusron; Mahardhika, Ahmad Gelora; Nasution, Addriana Della (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
The power relations between state institutions can be influenced by the state institutions that propose them, such as the appointment of United States judges who have ideological tendencies that are identical to the president. This study attempts to determine the ideology of constitutional judges and the political ideology of the President of the Republic of Indonesia through an analysis of the considerations of decisions and political parties. Is there a relationship between the political ideology of the president and constitutional judges in the consideration of decisions in judicial review cases? The design of this research is library research with a conceptual, legislative, and case study approach. Qualitative data analysis in the form of copies of Constitutional Court decisions supported by a study of related theoretical literature. The results of the study indicate that the ideology of constitutional judges seen from the considerations of their decisions is mostly moderate, although some considerations tend to be secular and Islamic. The political ideology of the president based on the ideology of the political parties supporting President Megawati and President Jokowi tends to be secular, while President Yudhoyono is nationalist-religious. The ideological relationship of constitutional judges proposed by the president is identical to the political ideology of President Megawati. Meanwhile, during the era of President Yudhoyono and President Jokowi, the ideology of constitutional judges in the consideration of their decisions was not identical to the ideology of the president's political party. This shows the independence of judges from the influence of the current political ruling ideology.